DERADIKALISASI ANAK-ANAK MANTAN TERORIS MELALUI PENDIDIKAN BERBASIS MULTIKULTURALISME - Arief Hidayat Afendi; Toto Santi Aji (Jurnal PGSD, 2020)
The spread of social conflicts that have occurred is clear evidence, such as the development of terrorist groups in various parts of the world in various forms. Victims of terrorism are not only those who died due to acts of terrorism, but including victims are families and children of terrorism perpetrators who do not know the activities carried out by their husbands or fathers. Coupled with the negative stigma and bullying behavior towards them sometimes leads to what is called "social reproduction". Khairul Ghazali, a former terrorist who carried out a robbery in CIMB Niaga, is well aware of the importance of education for children of former terrorists and families of terrorists. This qualitative research concludes that the Islamic Education Curriculum at the Daarusy Syifa Islamic Boarding School, Sei Mencirim Village, Kutalimbaru District, Deli Serdang North Sumatra uses a religious education approach taught in schools in a non-professional position as a social science. The religious education system aims solely to study religion as science and knowledge of society (learning to know about religion), not to instill belief and shape humans to obey their religion (learning to be religious persons). The implementation of multiculturalism-based Islamic education at the Daarusy Syifa Islamic Boarding School Darusy Syifaa Islamic Boarding School uses the concept of a natural school. The students in white robes and study turbans in a gazebo about 3x3 meters in size are deliberately placed under trees on the edge of rice fields and fish ponds. The view of the children of former terrorist actors and terrorist families towards the homogeneous and multicultural NKRI is actually no problem, it's just that the negative stigma and people's views of their fathers cause them to follow in the footsteps of their parents, because it is important for society to remove the stigma and abuse against them. most of whom are not involved such as children and families. Keyword: Deradicalization, Terrorism, Multiculturalism